2020
DOI: 10.1111/ahe.12570
|View full text |Cite
|
Sign up to set email alerts
|

Histological characterization of the maturation stages of the ovarian follicles of the goldfish Carassius auratus (Linnaeus, 1758)

Abstract: The goldfish (Carassius auratus) is a freshwater fish that belongs to one of the largest vertebrate families, the Cyprinidae, of the order Cypriniformes, being native from East Asia (Nelson, 2006). Selective breeding over the years led to the development of numerous breeds of goldfish, which vary in colour, body shape, size, fins and eye configuration, and are used for ornamental along with research purposes (Smartt, 2001). The goldfish is a cyprinid closely related to the most used fish in research laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, there is no information about the immunogenic potentials of the Gracilaria corticataas, as a one of the predominant seaweeds of Iran. Therefore, in this study, we used gold sh, Carassius auratus as a model sh (Li et al, 2016;Blanco et al, 2018;Ferrão et al, 2020) for evaluation of the in vivo effects of the dietary G. corticata extracts on sh growth, antioxidant and immune system.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no information about the immunogenic potentials of the Gracilaria corticataas, as a one of the predominant seaweeds of Iran. Therefore, in this study, we used gold sh, Carassius auratus as a model sh (Li et al, 2016;Blanco et al, 2018;Ferrão et al, 2020) for evaluation of the in vivo effects of the dietary G. corticata extracts on sh growth, antioxidant and immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Bluefin tuna late atresia is sometimes difficult to detect in standard histological sections of the ovary, especially long after the end of the spawning season, owing to their smaller size and poor contrast. Ferrão et al (2020) also reported low affinity of goldfish LAF to H&E staining. Under transmitted light microscopy, unstained histological sections show bluefin tuna LAF to be transparent or faintly brownish cell clusters (hence the term "brown bodies" commonly used in the literature).…”
Section: Discussionmentioning
confidence: 90%
“…Ferrão et al . (2020) also reported low affinity of goldfish LAF to H&E staining. Under transmitted light microscopy, unstained histological sections show bluefin tuna LAF to be transparent or faintly brownish cell clusters (hence the term “brown bodies” commonly used in the literature).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of these experiments can be very useful and interesting for producers of processed cheese, as their enrichment with gonads (caviar and milt) of Baltic herring (Clupea harengus membras) improves the nutritional properties of the cheese, which can have a positive impact on consumer demand Given the unique protein-lipid, vitamin-mineral composition of fish gonads, they are considered to be biologically valuable raw materials [1]. Therefore, the development of technology of processed cheese enriched with herring caviar and milt is relevant.…”
Section: Introductionmentioning
confidence: 99%